Structural Ultrasound of the Medial Temporal Lobe in Alzheimer’s Disease - Yilmaz, Rezzak; Pilotto, Andrea; Roeben, Benjamin; Preische, Oliver; Suenkel, Ulrike; Heinzel, Sebastian; Metzger, Florian G.; Laske, Christoph; Maetzler, Walter; Berg, Daniela (Ultraschall in der Medizin - European Journal of Ultrasound, 2017)
Purpose One of the anatomical hallmarks of Alzheimer’s disease (AD) is the atrophy of the medial temporal lobe (MTL), yet cost-effective and broadly available methodological alternatives to the current imaging tools for screening of this brain area are not currently available.Materials and Methods Using structural transcranial ultrasound (TCS), we attempted to visualize and measure the MTL, and compared the results of 32 AD patients and 84 healthy controls (HC). The MTL and the surrounding space were defined in the coronal plane on TCS. A ratio of the height of the MTL/height of the choroidal fissure (M/F) was calculated in order to obtain a regional proportion.Results An insufficient temporal bone window was identified in 22 % of the AD patients and 12 % of the HCs. The results showed that the ratio of M/F was significantly smaller in the AD group on both sides (p = 0.004 right, p = 0.007 left side). Furthermore, the M/F ratio made it possible to discriminate AD patients from HCs with a sensitivity of 83 % (right)/73 % (left) and a specificity of 76 % (right)/72 % (left) which is basically comparable to results published for magnetic resonance imaging. The measurements showed substantial intra/interrater reliability (ICC:0.79/0.69).Conclusion These results suggest that utilization of structural TCS may possibly constitute a cheap and easy-to-use supplement to other techniques for the diagnosis of AD. It may be especially useful as a screening tool in the large population of individuals with cognitive decline. Further studies are needed to validate this novel method.
Keywords: transcranial sonography; medial temporal lobe; Alzheimer's disease